Mouse ZGRF1 helicase facilitates DNA repair and maintains efficient fertility - Ernest Wee Kiat Lim; Smaragda Kompocholi; André Brannvoll; K. Stine V. Bagge; Jennifer R. Gruhn; Javier Martin-Gonzalez; Eliene Albers; Ian D. Hickson; Andrés López-Contreras; Michael Lisby (Heliyon)
The recently characterised human ZGRF1 helicase promotes genomic stability by facilitating DNA interstrand crosslink repair. In its absence, human cells exhibit greater sensitivity towards anti-cancer drugs such as mitomycin C and camptothecin. Moreover, the downregulation of ZGRF1 expression is associated with increased survival in cancer patients. These attributes point to ZGRF1 as a potential anti-cancer drug target. Here, we investigated the role of ZGRF1 in tumorigenesis using the mouse model. We generated a ZGRF1 mutant mouse and find that it is viable and displays normal development. However, at a cellular level, mouse embryonic fibroblasts exhibit sensitivity to ICLs and show elevated levels of the DNA damage marker γH2AX. In the absence of ZGRF1, the rates of tumorigenesis and tumour-free survival in Eμ-Myc and Trp53 knockout mice remained largely unaffected. These findings suggest a potential role for ZGRF1 in the proliferation of specific cancer types, highlighting avenues for further research in other cancer models. Additionally, beyond its known function in DNA repair, our study also reveals that ZGRF1 promotes meiotic recombination and that its loss results in reduced fertility in mice manifested as a 30 % reduction in meiotic crossovers and a 15 % reduction in litter size.